Pengaruh intervensi pijat tui na dan temulawak (curcuma xanthorrhiza) terhadap nafsu makan balita - Subur , Rina Yuliana; Arti, Reka Saka Dwi; Mustikawati, Eka Desita; Susilowati, Putry; Agustina, Marlin; Sari, Agustina; Wulandari, Ratna (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Introduction: Decreased appetite in toddlers can increase the risk of growth disorders and nutritional problems, including malnutrition and stunting. Non-pharmacological interventions such as Tui Na massage and supplementary foods made from Javanese ginger (Curcuma xanthorrhiza) can be alternatives to help increase children's appetite. Purpose: To analyze the effect of Tui Na massage and supplementary foods made from Javanese ginger on improving appetite in toddlers. Method: This quantitative study used a quasi-experimental design with a one-group pretest-posttest. The subjects were four 4-year-old toddlers experiencing eating difficulties. Two toddlers received Tui Na massage, while the other two received supplementary foods made from Javanese ginger. The interventions were administered for 14 days. Appetite was measured using the Children's Eating Behavior Questionnaire (CEBQ) through pre- and post-intervention assessments. Data were analyzed descriptively by comparing appetite scores at the pre- and post-test stages. Results: There was an increase in appetite scores after both interventions. The Tui Na massage group experienced an average increase in scores of 6.5 points, while the ginger supplement group experienced an average increase in scores of 13 points. The increase in appetite scores in the ginger group was higher than in the Tui Na massage group. Conclusion: Tui Na massage and ginger supplement both showed a positive effect on increasing toddlers' appetite. However, the ginger supplement showed a greater increase in scores. Ginger has the potential to be a more optimal non-pharmacological intervention to help address appetite issues in toddlers. Suggestion: Providing ginger-based foods can be considered as the primary non-pharmacological intervention to increase appetite in toddlers, while Tui Na massage can be used as a supportive therapy. It is hoped that healthcare professionals and parents will implement both interventions consistently and according to the child's needs. Keywords: Appetite; Curcuma Xanthorrhiza; Ginger; Herbal Supplementation; Toddlers; Tui Na Massage. Pendahuluan: Penurunan nafsu makan pada balita dapat meningkatkan risiko gangguan pertumbuhan dan masalah gizi, termasuk gizi kurang dan stunting. Upaya nonfarmakologis seperti pijat Tui Na dan pemberian makanan tambahan berbahan temulawak (Curcuma xanthorrhiza) dapat menjadi alternatif untuk membantu meningkatkan nafsu makan anak. Tujuan: Untuk menganalisis pengaruh intervensi pijat Tui Na dan pemberian makanan tambahan berbahan temulawak terhadap peningkatan nafsu makan pada balita. Metode: Penelitian kuantitatif dengan desain quasi experiment tipe one group pretest-posttest. Subjek penelitian terdiri atas empat balita berusia 4 tahun yang mengalami kesulitan makan. Dua balita mendapat intervensi pijat Tui Na, sedangkan dua balita lainnya mendapat makanan tambahan berbahan temulawak. Intervensi diberikan selama 14 hari. Nafsu makan diukur menggunakan Children’s Eating Behaviour Questionnaire atau CEBQ melalui penilaian sebelum dan sesudah intervensi. Data dianalisis secara deskriptif dengan membandingkan skor nafsu makan pada tahap pre-test dan post-test. Hasil: Adanya peningkatan skor nafsu makan setelah pemberian kedua intervensi. Kelompok pijat Tui Na mengalami peningkatan rata-rata skor sebesar 6,5 poin, sedangkan kelompok makanan tambahan berbahan temulawak mengalami peningkatan rata-rata skor sebesar 13 poin. Peningkatan skor nafsu makan pada kelompok temulawak lebih tinggi dibandingkan kelompok pijat Tui Na. Simpulan: Pijat Tui Na dan makanan tambahan berbahan temulawak sama-sama menunjukkan pengaruh positif terhadap peningkatan nafsu makan balita. Namun, makanan tambahan berbahan temulawak menunjukkan peningkatan skor yang lebih besar. Temulawak berpotensi menjadi intervensi nonfarmakologis yang lebih optimal dalam membantu mengatasi masalah nafsu makan pada balita. Saran: Pemberian makanan olahan temulawak dapat dipertimbangkan sebagai intervensi nonfarmakologis utama untuk meningkatkan nafsu makan pada balita, sementara pijat Tui Na dapat digunakan sebagai terapi pendukung. Diharapkan tenaga kesehatan dan orang tua dapat menerapkan kedua intervensi ini secara konsisten dan sesuai dengan kebutuhan anak. Kata Kunci: Balita; Curcuma Xanthorrhiza; Nafsu Makan; Pijat Tui Na; Temulawak; Suplementasi Herbal.